PROCEEDINGS OF SESSIONS OF THE SECTION OF CARDIOVASCULAR SURGERY OF THE PIROGOV SURGICAL SOCIETIES № 245–247 - Article Editorial (Вестник хирургии имени И.И. Грекова)
Proceedings of sessions of the section of cardiovascular surgery of the Pirogov Surgical Societies № 245–247.